The Influence Of Professional Skeptism, Independence, Audit Fee, And Remote Audit Process On Auditor Performance - Rama, Radian Sri; Darmayanti, Novi; Kusmayasari, Dewi; Suhardiyah, Martha; Abdullah, Zailani (Politeknik Ganesha Medan, 2024)
This study aims to analyze how much influence professional skepticism, independence, audit fees and remote audit processes have on auditor performance. The population in this study is KAP in Surabaya and Malang, 60 responden. The sampling method used in this study are saturated samples. Collecting data in this study by distributing questionnaires to respondents. The samples used in this study were 60 auditors who worked in 11 Public Accounting Firms (KAP) in the cities of Surabaya and Malang. The analytical method used is multiple linear regression analysis and processed using SPSS version 25. The results of this study indicate that partially professional skepticism and audit fees have a significant effect on auditor performance. Meanwhile, independence and the remote audit process have no significant effect on auditor performance. Simultaneously, professional skepticism, independence, audit fees and remote audit processes have a significant effect on auditor performance. This research is in accordance with auditing theory and has implications for how auditors' performance in KAP is more skeptical and independent, so that it can help auditors to be more vigilant in detecting fraud.